Strategic Campaigns and Redistributive Politics - Christian Schultz (Center for Economic Studies and ifo Institute (CESifo), 2003)
The paper investigates strategic campaigning in a model of redistributive politics in a society with many groups and two parties. Campaigns are informative, and parties can target campaigns to different groups. Voters are uncertain about whether parties fabor special groups. The parties will seek to target campaings at groups where most votes are gained by informating about policies. In equilibrium campaigning will be most intensive in groups where the uncertainty is largest and where voters are most mobile. These groups will therefore be very well informed about policy and will accordingly be favored by the parties policies.
Keywords: 330; political economy; redistribution; information